Simple mini Walkman / Norrahimah Abd Rahim and Rusni Othman - Abd Rahim, Norrahimah; Othman, Rusni (2003)
Our project is called simple mini Walkman. The main purpose is not to tune a radio, but it just to get the signal sound in cassette player. In general, this simple mini Walkman required one IC, two transistor, speaker and etc. In this project we use TDA 2002 IC’s. It is low cost equipment and easy to use. The equipment is also simple. This project circuit is not complicated. The circuit can be divided into two stage, the first stage is pre-amplifier and the second stage is power amplifier. This two stage have each own function. More information about the circuit will be discussed later. Preamplifier is a low-level signal amplifier, which precedes a large signal amplifier on power amplifier output. That is the reason why we choose the simple mini Walkman.